MTTR, MTBF, and OEE Analysis of a Blown Film Extrusion Machine for Preventive Maintenance Optimization - Elisabet Priska Arkadewi Kononis; Desrina Yusi Irawati; David Andrian (Heuristic, 2026)
Blown Film Extrusion Machines are critical equipment in the plastic manufacturing industry, where machine reliability and maintenance effectiveness significantly affect productivity and product quality. This condition was observed in a plastic manufacturing plant in Sidoarjo Regency, where maintenance activities are still predominantly reactive and lack a structured preventive maintenance system. This study aims to analyze the performance and reliability of Blown Film Extrusion Machines and to determine critical components as a basis for optimizing preventive maintenance through the integration of Overall Equipment Effectiveness (OEE), Mean Time Between Failure (MTBF), and Mean Time to Repair (MTTR). The research methodology employs a quantitative descriptive approach with an applied case study design. Data collection was conducted through direct observation of 11 Blown Film Extrusion Machines, including data on downtime, failure frequency, repair duration, operating time, and production output consisting of good and defective products. Data processing involved calculating OEE to evaluate machine effectiveness, MTBF to measure reliability, and MTTR to assess repair efficiency. Downtime analysis was also performed to identify components contributing most significantly to production stoppages. The results indicate an overall OEE value of 73%, an MTTR of 229.89 minutes, and an MTBF of 1,421.67 minutes. The PLC, chiller, and bearing were identified as the main contributors to downtime. This study concludes that low machine effectiveness is caused by frequent failures and prolonged repair times, highlighting the need to prioritize preventive maintenance on critical components to improve machine reliability and effectiveness.